Global climate change and the resurgence of tropical disease: An economic approach - Douglas Gollin; Christian Zimmermann (Institute for the Study of Labor (IZA), 2010)
We study the impact of global climate change on the prevalence of tropical diseases using a heterogeneous agent dynamic general equilibrium model. In our framework, households can take actions (e.g., purchasing bednets or other goods) that provide partial protection from disease. However, these actions are costly and households face borrowing constraints. Parameterizing the model, we explore the impact of a worldwide temperature increase of 3° C. We find that the impact on disease prevalence and especially output should be modest and can be mitigated by improvements in protection efficacy.
Keywords: I1; O11; E13; E21; Q54; 330; DSGE models; climate change; tropical diseases; incomplete markets; Klimaveränderung; Tropenkrankheit; Gesundheitsvorsorge; Privater Haushalt; Verschuldungsrestriktion; Dynamisches Gleichgewicht; Simulation; Welt